The good thief : a novel - Tinti, Hannah (New York : Dial Press Trade Paperbacks, 2009)
Young Ren, an orphan in nineteenth-century New England, is rescued from the orphanage by Benjamin Nab, who claims to be Ren's brother; but as time goes on Ren begins to question who he can and cannot trust.
Wilson's Fiction, March 2009
Booklist starred, June 2008
Publisher's Weekly, May 2008
Kirkus Starred, June 2008
New York Times, September 2008
Teacher Librarian, December 2009
Keywords: Orphans -- Fiction; New England -- Fiction; United States -- History -- 1783-1865 -- Fiction; Orphans -- Fiction; New England -- Fiction; United States -- History -- 1783-1865 -- Fiction; Historical fiction; Historical fiction